Artikel Factors associated with mother's knowledge of oxytocin massage to expedite milk production at midwife andina’s independent practice - Citra Dewi, Ayu Devita; Sastri, Nen (International Journal on Health and Medical Sciences, 2023)
Knowledge is the result of "knowing" and this occurs after people perceive an object. Breastfeeding is a natural process that occurs and is carried out by women after giving birth. Massage is one solution to overcome the uneven production of ASI. Massage is massage along the spine (vertebrae) to the fifth-sixth ribs and is an attempt to stimulate the hormones prolactin and oxytocin after childbirth. This research is a quantitative research with cross sectional research design. The population in this study were all postpartum and breastfeeding mothers. The variables in this study were: Independent Variables (Age, Education, Occupation, Family Support) Dependent Variables (Mother's Knowledge about Oxytocin Massage). The results of the study found that there was a significant relationship between age and maternal knowledge. The statistical test results obtained p value = 0.036 more smaller than α = 0.05, there is no significant relationship between work and mother's knowledge with statistical test results p value = 0.091 greater than α = 0.05, there is a significant relationship between education and mother's knowledge statistical test results obtained value p value = 0.091 greater than α = 0.05, there is a significant relationship between education and mother's knowledge statistical test results obtained p value = 0.01 less than α = 0.05.